2016
DOI: 10.1186/s40644-016-0088-y
|View full text |Cite
|
Sign up to set email alerts
|

C-arm computed tomography and volume perfusion computed tomography (VPCT)-based assessment of blood volume changes in hepatocellular carcinoma in prediction of midterm tumor response to transarterial chemoembolization: a single center retrospective trial

Abstract: BackgroundThis study aims to evaluate immediate changes in perfusion parameters in hepatocellular carcinoma (HCC) to transarterial chemoembolization (TACE) in C-arm computed tomography (CT) and volume perfusion CT (VPCT) and prediction of midterm tumor response.MethodsTwenty-five patients (median age 66, range 61 to 75 years) with 62 HCC lesions undergoing TACE received immediate pre- and post-interventional assessment by C-arm CT and VPCT. Cross-sectional imaging was analyzed at baseline and approximately 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Although criteria have been made for the prognosis of HCC patients, such as BCLC stage for risk stratify and Child-pugh class for liver function staging, predictive factors for treatment response of DEB-TACE are still not well established. C-arm CT and volume perfusion CT (VPCT) for blood volume assessment have been reported by a prior study that they are able to predict the midterm tumor response of patients [ 21 ]. Furthermore, a study illustrates that tumor heterogeneity and tumor enhancement more than 50% are correlated with CR in HCC patients after DEB-TACE therapy [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although criteria have been made for the prognosis of HCC patients, such as BCLC stage for risk stratify and Child-pugh class for liver function staging, predictive factors for treatment response of DEB-TACE are still not well established. C-arm CT and volume perfusion CT (VPCT) for blood volume assessment have been reported by a prior study that they are able to predict the midterm tumor response of patients [ 21 ]. Furthermore, a study illustrates that tumor heterogeneity and tumor enhancement more than 50% are correlated with CR in HCC patients after DEB-TACE therapy [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As tumour blood perfusion coefficient (x b ) has been reported within a wide range of values: 0.0027 s -1 [32], 0.0053 s -1 [43], 0.0069 s -1 [45], 0.0096 s -1 [33], 0.011 s -1 (63.8 mL/100g min À1 , [46]) and 0.009 s -1 (510 mL kg À1 min À1 , [30]), we chose a value of 0.009 s -1 as it was the reference we used for healthy tissue and agreed with Aramburu et al [45], who suggested that perfusion in healthy tissue is different from that of tumour tissue. While healthy tissue is supplied through the portal vein and hepatic artery, a tumour is exclusively supplied from the hepatic artery, which could mean the blood perfusion rate is higher in healthy tissue than in the tumour.…”
Section: Tissue Characteristicsmentioning
confidence: 98%
“…Again, we assessed the time-step suitability by an analogous sensitivity analysis. Table 1 shows the parameter values used in the model [29][30][31][32][33][34][35][36][37][38][39][40][41]. Healthy liver electrical conductivity (r) was set to 0.2 S m À1 at a reference temperature of 37 C, within the range of values reported in the literature: 0.132 S m À1 [29], 0.143 S/m [30] and 0.260 S m À1 [42].…”
Section: Solvermentioning
confidence: 99%
See 1 more Smart Citation
“…PBV has been shown to correlate with other parameters of perfusion measurement like volume perfusion CT [ 14 ] and to enable the visual and quantitative assessment of tumor-perfusion directly during the angiographic work-up procedure. Furthermore, the acquisition of 3D C-arm CTs improve the detection of aberrant vessels and identification of vascular territory supply compared to regular digital subtraction angiography images and has become part of the routine work-up in various centers [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%